2022
DOI: 10.3390/polym14112259
|View full text |Cite
|
Sign up to set email alerts
|

Self-Healable and Recyclable Dual-Shape Memory Liquid Metal–Elastomer Composites

Abstract: Liquid metal (LM)–polymer composites that combine the thermal and electrical conductivity of LMs with the shape-morphing capability of polymers are attracting a great deal of attention in the fields of reconfigurable electronics and soft robotics. However, investigation of the synergetic effect between the shape-changing properties of LMs and polymer matrices is lacking. Herein, a self-healable and recyclable dual-shape memory composite, comprising an LM (gallium) and a Diels–Alder (DA) crosslinked crystalline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 67 publications
0
16
0
Order By: Relevance
“…Range from highly crosslinked to no crosslinks Slightly crosslinked Range from being flexible to rigid Flexible and elastic Wide range of glass transition temperatures Typically low (sub-zero) glass transition temperature 2022, 14, x FOR PEER REVIEW 2 of 21 permanent shape from the temporary deformations upon simultaneous disclosure to various (even multiple) stimuli without additional mechanical effort. Typically, SMPs exhibit at least two phases: the first is a stable form that stabilises the SMP and is responsible for the retention of the original shape and the second that responds to the external trigger [15][16][17][18][19][20][21][22][23][24][25]. SMPs can be categorized into one of four types depending on their chemical structure: thermosets, rubbers, thermoplastics, and block copolymers.…”
Section: Polymer Elastomermentioning
confidence: 99%
See 2 more Smart Citations
“…Range from highly crosslinked to no crosslinks Slightly crosslinked Range from being flexible to rigid Flexible and elastic Wide range of glass transition temperatures Typically low (sub-zero) glass transition temperature 2022, 14, x FOR PEER REVIEW 2 of 21 permanent shape from the temporary deformations upon simultaneous disclosure to various (even multiple) stimuli without additional mechanical effort. Typically, SMPs exhibit at least two phases: the first is a stable form that stabilises the SMP and is responsible for the retention of the original shape and the second that responds to the external trigger [15][16][17][18][19][20][21][22][23][24][25]. SMPs can be categorized into one of four types depending on their chemical structure: thermosets, rubbers, thermoplastics, and block copolymers.…”
Section: Polymer Elastomermentioning
confidence: 99%
“…A category of smart materials, SMEs react to external stimuli such as temperature, pressure, electromagnetic fields, chemicals (and pH), water, light, and so on. The responsive physical properties could be stiffness, shape, and damping, among others [1,9,14,24,[40][41][42]. A recent SME was developed by Rim et al (2022) [43].…”
Section: Polymermentioning
confidence: 99%
See 1 more Smart Citation
“…The LM-PU (polyurethane) composite exhibits a bilayer structure and achieves excellent shape-morphing abilities due to the phase transitions of LM and crystalline PU elastomers. 20 Biphasic liquid metal mixtures and their applications in flexible and stretchable electronics are highlighted in this article. Additionally, the properties and tuning methods of LM alloys (biphasic LM mixture with solid metal particles) and composites (biphasic LM mixture with elastomers) with organic materials and patterning techniques for circuit fabrication are summarized.…”
Section: Introductionmentioning
confidence: 99%
“…In general, LCEs require external heating elements to facilitate shape-change actuation. Previous research reported LCE composites that were electrically actuated by Joule heating using conductive paths such as flexible metal wires [ 13 , 14 , 15 , 16 ], silver ink/paste [ 17 ], carbon coatings [ 18 ], and encapsulated liquid metal [ 19 , 20 ]. These approaches have proven to be effective for repeatable actuation.…”
Section: Introductionmentioning
confidence: 99%